Depressive symptoms in people with vision impairment: a cross-sectional study to identify who is most at risk. Issue 1 (17th January 2019) - Nollett, Claire; Ryan, Barbara; Bray, Nathan; Bunce, Catey; Casten, Robin; Edwards, Rhiannon Tudor; Gillespie, David; Smith, Daniel J; Stanford, Miles; Margrain, Tom H
Abstract : Objective: To identify the risk factors for significant depressive symptoms in people with visual impairment in England and Wales to provide information on who is most at risk and to whom support services could be targeted in future. Design: A cross-sectional study using baseline data from a pragmatic randomised controlled trial. Setting and participants: 990 participants aged 18 or over attending 1 of 14 low-vision rehabilitation primary care optometry-based clinics in South Wales or two hospital clinics in London. Outcome measure: A score of ≥6 on the Geriatric Depression Scale-15 was classed as clinically significant depressive symptoms. Results: In a multivariable logistic regression model, significant depressive symptoms were associated with age (adjusted OR (AOR)=0.82, 95% CI: 0.66 to 0.90, p<0.001), ethnicity (AOR non-white compared with white=1.72, 95% CI: 1.05 to 2.81, p=0.031), total number of eye conditions (AOR for two vs one condition=0.98, 95% CI: 0.67 to 1.43; three or more vs one condition=0.34, 95% CI: 0.15 to 0.75, p=0.026), self-reported health (AOR for excellent vs poor=0.01, 95% CI: 0.00 to 0.12; very good vs poor=0.06, 95% CI: 0.03 to 0.13; good vs poor=0.14, 95% CI: 0.08 to 0.24; fair vs poor=0.28, 95% CI: 0.18 to 0.46, p<0.001) and self-reported visual functioning (AOR=1.45, 95% CI: 1.31 to 1.61, p<0.001). Conclusion: Younger age, a non-white ethnicity, fewer eye conditions and poorer self-reported health and visual function are risk factors for significant depressive symptoms in this population. Trial registration number: ISRCTN46824140; Pre-results.